The Pyrogeography of Methane Emissions from Seasonal Mosaic Burning Regimes in a West African Landscape - Paul Laris; Moussa Koné; Fadiala Dembélé; Christine M. Rodrigue; Lilian Yang; Rebecca Jacobs; Quincy Laris; Facourou Camara (Fire, 2023)
People have set fire to the savannas of West Africa for millennia, creating a pyrogeography. Fires render the landscape useful for many productive activities, but there is also a long history of efforts to regulate indigenous burning practices. Today, savanna fires are under scrutiny because they contribute to greenhouse gas emissions, especially methane. Policy efforts aimed at reducing emissions by shifting fire regimes earlier are untested. Most emissions estimates contain high levels of uncertainty because they are based on generalizations of diverse landscapes burned by complex fire regimes. To examine the importance of seasonality and other factors on methane emissions, we used an approach grounded in the practices of people who set fires. We conducted 107 experimental fires, collecting data for methane emissions and a suite of environmental variables. We sampled emissions using a portable gas analyzer, recording values for CO, CO2, and CH4. The fires were set both as head and backfires for three fire periods—the early, middle, and late dry season. We also set fires randomly to test whether the emissions differed from those set according to traditional practices. We found that methane emission factors and densities did not increase over the dry season but rather peaked mid-season due to higher winds and fuel moisture as well as green leaves on small trees. The findings demonstrate the complexity of emissions from fires and cast doubt on efforts to reduce emissions based on simplified characterizations of fire regimes and landscapes.